Incidence of Postoperative Acute Kidney Injury and its Effect on Long-term Survival after Coronary Artery Bypass Graft Surgery: a Meta-analysis - Patrícia Maria Martins de Sousa (2022)
Introduction: We aimed to estimate the impact of AKI on long-term and early survival, AKI incidence and its potential effect modifiers, in patients who underwent isolated coronary artery bypass graft (CABG) surgery, through a meta-analysis of observational studies. Evidence acquisition: A literature search was conducted to select observational studies with follow-up ≥ 1 year. Outcomes were collected through hazard ratios (HR) and their variance, frequencies, or odds ratios (OR). Random effects models were used to compute combined statistical measures and 95% confidence intervals (CI), through generic inverse variance method (time-to-event), Mantel-Haenszel method (binary events) or generalized linear mixed-effects model and logit-transformed proportions of AKI (incidence). Evidence synthesis: From 7369 records screened, 1083 studies were selected for eligibility assessment. Out of these, 13 retrospective observational cohort studies comprising 63209 patients were included. AKI incidence ranged from 0.57% to 54% and pooled analysis evidenced an incidence of 16%, 95%CI: 8 - 29% and a high heterogeneity (I2=100%). Postoperative AKI is associated not only with a higher probability of early mortality (pooled OR: 7.59, 95%CI: 3.18-18.15, p<0.01) but also with higher risk of long-term mortality (pooled HR: 2.23, 95%CI: 1.83-2.70, p<0.01). Age, cardiopulmonary bypass, and length of follow-up were not identified as effect modifiers of AKI impact on long-term mortality. Conclusions: AKI is a frequent complication after isolated CABG surgery, although its incidence shows high variation. It is not only associated with higher risk of early mortality, but also with a significant drop in long-term survival, which may be multifactorial.